Diversifikasi produk olahan ikan Nila Salin (Oreochromis niloticus) dan pengenalan alat peniris minyak abon di Kelurahan Pangkalan Sesai - Dessy Yoswaty; Rifardi Rifardi; Mubarak Mubarak; Elizal Elizal (Unri Conference Series: Community Engagement, 2022)
The activities of the Community Partnership Program (PKM) in 2022 are an alternative in the processing of saline tilapia. The activities given to PKK/household partners and members in Pangkalan Sesai Village were diversification of processed tilapia saline products (such as shredded and snack churros) and identification of shredded oil slicers. The objectives were to increase the diversification of processed saline tilapia products (such as shredded and snack churros) and introduce the capacity of shredded spinners for food safety. The benefits are introducing diversification techniques for processed saline tilapia products (such as shredded and snack churros) and the introduction of shredded oil slicers to improve science and technology and partner skills. The target audience involved numbered 20 people. The results of PKM activities showed that the partners welcomed well, were very enthusiastic in receiving the transfer of science and technology and the diversification skills of processed saline tilapia products (such as shredded and snack churros) and the introduction of shredded oil slicers. Mitra conveyed the perception of PKM activities, namely 11 people (55.5%) expressed Strong agreement, 8 people (38.5%) agreed and 1 person (6.0%) stated Neutral. Partners can be motivated and willing to practice diversification techniques for processed saline tilapia products.